2019
DOI: 10.1038/s41467-019-08569-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal stiffening in synthetic hydrogels

Abstract: Although common in biology, controlled stiffening of hydrogels in vitro is difficult to achieve; the required stimuli are commonly large and/or the stiffening amplitudes small. Here, we describe the hierarchical mechanics of ultra-responsive hybrid hydrogels composed of two synthetic networks, one semi-flexible and stress-responsive, the other flexible and thermoresponsive. Heating collapses the flexible network, which generates internal stress that causes the hybrid gel to stiffen up to 50 times its original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 44 publications
1
78
0
Order By: Relevance
“…The 2D shape of TiNSs, which eliminates the possibility of entanglement, may be the reason for the excellent rapidity and reversibility of the thermal response of TiNS-Gel. These properties appear to be superior to those of conventional hydrogels based on 1D materials such as organic polymers or nanofibers 1 13 . Although poly( N -isopropylacrylamide) and related organic polymers have long been the components of choice for smart soft materials 42 , 43 , we have demonstrated that TiNS can serve as an alternative to such organic polymers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The 2D shape of TiNSs, which eliminates the possibility of entanglement, may be the reason for the excellent rapidity and reversibility of the thermal response of TiNS-Gel. These properties appear to be superior to those of conventional hydrogels based on 1D materials such as organic polymers or nanofibers 1 13 . Although poly( N -isopropylacrylamide) and related organic polymers have long been the components of choice for smart soft materials 42 , 43 , we have demonstrated that TiNS can serve as an alternative to such organic polymers.…”
Section: Discussionmentioning
confidence: 93%
“…This seems considerably difficult because living organisms usually consist of water-rich flexible solids with a structural hierarchy that are capable of responding to stimuli, unlike inorganic materials, which generally exhibit poor processability, low flexibility, and a lack of responsiveness. Indeed, previous studies on biomimetic soft materials have almost exclusively involved the use of organic constituents [1][2][3][4][5][6][7][8] , as typically represented by mechanically adaptive hydrogels based on thermoresponsive organic polymers such as poly(N-isopropylacrylamide) [7][8][9][10][11][12][13] . However, if counterparts of these hydrogels consisting entirely of inorganic materials were to become available, they could expand the scope of materials science by adopting a complementary role to organic-based biomimetic soft materials in providing such characteristics as good mechanical properties, long-term durability, and low environmental burdens [14][15][16] .…”
mentioning
confidence: 99%
“…cell cytoskeletons) with properties such as structural support and repetitive energy dissipation. [8][9][10][11][12][13] For example, a-helical lamin protein domains that define the lattice-like network of the cell's nucleus, provide both crucial structural support, as well as aiding in the coupling of mechanical signals to complex biochemical processes in the cell. 14 The staggered architecture in a collagen microfibril permits energy dissipation through molecular sliding, rather than snapping and can withstand GPa of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Hofmeister ions, proposed in 1888 [ 24 ], are arranged in order of the ability of salts to precipitate certain proteins in aqueous solutions. Note that PNIPAAm also follows this trend associated with the LCST [ 25 , 26 , 27 , 28 , 29 ]. Specifically, as the concentration of Hofmeister anions increases, the LCST of PNIPAAm decreases, and the degree of the decrease differs depending on the type of anion.…”
Section: Introductionmentioning
confidence: 91%